Local adaptation at a small geographic scale observed in Juniperus excelsa populations in southern Turkey - Yücedag C (Italian Society of Silviculture and Forest Ecology (SISEF), 2021)
Juniperus excelsa is one of the most common tree species and has a wide geographical and altitudinal distribution in Turkey. It is also resistant to drought and frost damages and can cope with poor soils. In this study, we explore whether there are any differences among eight J. excelsa populations from a narrow geographic region grown in a common garden test site in terms of growth and contents of photosynthetic pigments, proline and nutrients of their 10-year-old saplings. Phenotypic trait differentiation (QST) at all traits, FST at neutral SSRs among six of the populations and associations of traits with environmental conditions at provenance regions were also analysed to test for patterns of local adaptation. Sapling traits of eight J. excelsa populations of from Lakes District in Turkey at the test site showed that populations significantly differed for growth, photosynthetic pigments, proline and nutrient contents. The mean height and diameter of 10-year-old saplings were found as 94.5 cm and 41.6 mm, respectively. Egirdir-Barla and Sütçüler-Tota populations showed the highest performance for the majority of traits at age 10 compared to all other populations. Nutrient contents in leaves were generally in the sufficiency range reported for plant growth. Considering photosynthetic pigments and proline, it could be concluded that the populations were not exposed to severe stress. Among the environmental variables, the best predictors of growth were annual mean minimum temperature and soil texture at the populations’ origin, accounting for 49% of the variation in height and diameter, respectively. Also, higher phenotypic trait differentiation for most traits than genetic differentiation at neutral genetic markers suggests local adaptation at a small geographic scale. The present study revealed adaptive divergence between populations at a small geographic scale. However, environmental similarity between region of origin and test site was not a good indicator of growth-related traits. The results can be used in the early selection of provenances for J. excelsa for plantation establishment.